HUBUNGAN ANTARA OBESITAS SENTRAL, ASUPAN ENERGI, LEMAK DAN NATRIUM DENGAN KEJADIAN HIPERTENSI - , SYEFIRA SALSABILA ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Backgrounds: Hypertension is one of public health problem with high prevalence in Indonesia. In the future, hypertension may increase number of morbidity and mortality. Hypertension is caused by the interaction of various risk factor. One of the factors causing hypertension is obesity and food intake. Objective: To know the relationship between central obesity, energy, fat, and natrium intake with hypertension. Method: This study is observational with the cross sectional design. This study was collectedat GMC Health Center Yogyakarta in February until April 2014. Sample collected using consecutive sampling method with 110 respondent who did the general check up at GMC Health Center. Data of central obesity using waist circumference. Data energy, fat and natrium intake was got by using food frequency. Analysis was carried out in stages include univariate analysis, bivariate analysis using chi square test, and multivariate analysis using logistic regression test. Result : Result of this study shows that 62,7% of the subject had central obesity, 28,2% of the subject had hypertension. The result of chi square test showed that central obesity had significant association with hypertension (RP = 1,36, CI 95% 0,15 â 0,85 and p = 0,017), fat intake with hypertension (RP = 2,64 , CI 95% 1,08 â 6,44 and p = 0,03), natrium intake and hypertension (RP = 2,96 , CI 95% 1,25 â 6,97 and p = 0,012). There is no significant association energy intake with hypertension ( RP = 0,5 , CI 95% 0,22 â 1,17 and p = 0,11). The result of logistic regression showed that fat intake was dominant risk factor for the prevalence of hypertension. Conclusion: Central obesity, fat and natrium intake were a risk factors for hypertension